Reprodutibilidade de padrões morfológicos no teste de autoanticorpos contra antígenos celulares (FAN-HEp-2) em diferentes substratos - Silva, Monica De Jesus [UNIFESP] (2020)
The indirect immunofluorescence assay on HEp-2 cells (HEp-2 IFA) is the gold standard method for anti-cellular (AC) antibody screening. Cell culture and fixation methods influence in the distribution and preservation of autoantigens, therefore affect in antigen preservation and distribution, as well as the AC patterns (1,2). Objective: We aimed to evaluate the non-reproducibility phenomenon of HEp-2 IFA results in different HEp-2 slide brands from patients with Systemic Autoimmune Disease (SAD), patients with Non-Autoimmune (NAD), and samples from healthy individuals. Methods: Were evaluated 868 serum samples from 275 patients with SAD, 293 patients with NAD, and 300 samples from healthy blood donors (HBD).Samples were processed at 1:80 dilution according to standard procedure on four HEp-2 slide brands. The tests were interpreted by three experienced independent blinded observers. The agreement among slides was determined using proportional weights according to the number of concordant slides in each sample, yielding a weighted score (ranging from 1 to 100) in specific groups of samples. The qualitative variables were analyzed by the Chi-square test and concordance was analyzed using the Kappa test. All data were analyzed using SPSS20.0 software at a significance level of p <0.05. Results: 402 samples were non-reagent in all slide brands and, therefore, were considered devoid of autoantibodies and eliminated from further analysis. The global reactivity agreement score obtained forth e remaining 466 samples (238 SAD, 119 NAD, and 109 HBD) was considered regular (74, 5). The nuclear compartment showed the highest agreement score (83,6), followed by the metaphase plate (78,9), cytoplasm (77,4) and nucleolus (72,4).Among the clinical groups, the agreement score was higher in SAD (78,0) than in NAD (70,6) and HBD (71,3). Samples with low reactivity (+/4) had higher discordance rates than high intensity samples (++++/4). In the SAD group the discordance for nuclear reactivity was 12.5% for ++++/4 samples, as opposed to 95.6% for +/4 samples, and the same was observed with NAD and HBD samples. The most robust nuclear patterns (higher concordance rate) were, Centromeric (score 78,4), Multiple Nuclear Dots (score73,6), Coarse Speckled (score71,3), and Homogeneous (score 67,9). Among the cytoplasmic patterns, the Reticular Cytoplasmic was more robust (68, 6). Conclusion: The phenomenon of non-reproducibility in the HEp-2 IFA among different slide brands occurs with highest frequency with samples with low intensity.